A COMPARATIVE ANALYSIS OF THE ORIGINAL AND THE TRANSLATIONS OF THE ESSAY "THE STRANGER" (L'ETRANGER) BY ALBER CAMUS. (Scientific journal of the Fergana State University, 2024)
This article raises the issue of studying the influence of translations of Albert Camus’s works into Russian and Uzbek on reception and draws reasonable conclusions. If knowledge of the cultural and spiritual wealth of the peoples of the world requires a special look at one’s own national heritage, then mutual comparison creates the opportunity to correctly evaluate it. Today, with the help of translators, ties between national literatures are strengthened, the processes of interaction and mutual enrichment are accelerated. It should be noted here that interest in French culture, language and literature in Uzbekistan has always been great. In particular, it is noted that the importance of translating famous and famous works of French literature from the original version into the Uzbek language, along with the Russian translation, has increased significantly. The article substantiates the originality of Albert Camus's essay “The Stranger” “The Stranger”; when comparing the translations of Dahl, Nemchinova and Ahmad Azam, the reception of the work in different languages is different. Some parts of the original version of the work were taken out, and the translations of 2 translators into Russian and the Uzbek translation into Russian were compared and analyzed.